Sierra Leone Multiple Indicator Cluster Survey 2017 - Statistics Sierra Leone (Statistics Sierra Leone, 2018)

Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)

Sierra Leone Media Landscape Report - BBC Media Action (2018)

GSMA Mobile Connectivity Index | Sierra Leone - GSMA (2018)
The GSMA Mobile Connectivity Index is a global mobile connectivity and digital economy guide covering 150 countries and 7 sub-regions

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Wright, Dr. Cream (Global Partnership for Education; World Bank, 2018)

FQSE – Free Quality School Education - Ministry of Basic and Senior Secondary Education Sierra Leone (Ministry of Basic and Senior Secondary Education Sierra Leone, Government of Sierra Leone, 2018)

Keynote Address by His Excellency President Julius Maada Bio on the theme of: "Education for Development" at the launch of the Free Quality School Education Programme - Maada Bio, Julius (2018)

Sierra Leone population 2020 - WorldPop (2018)
RF-based gridded population distribution datasets produced in the framework of the Global Project - Funded by The Bill and Melinda Gates Foundation (OPP1134076)
Keywords: Population distribution, Population, Dasymetric disaggregation

Education for Development - Maada Bio, Julius (2018)

Proportion of schools with access to basic facilities, all schools - UNESCO (2018)

Mobile Learning Lab Evaluation & Analysis - 60 Million Girls (60 million girls, 2018)

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - DFID (2018)

Incidence of malaria (per 1,000 population at risk) - Sierra Leone, Sub-Saharan Africa (excluding high income) | Data - World Bank (2018)

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Teaching Service Commission (Global Partnership for Education, 2018)

The Economic Lives of Young Women in the Time of Ebola: Lessons from an Empowerment Program - Bandiera, Oriana; Buehren, Niklas; Goldstein, Markus; Rasul, Imran; Smurra, Andrea (World Bank, 2018)
We evaluate an intervention to raise young women’s economic empowerment in Sierra Leone, where women frequently experience sexual violence and face multiple economic disadvantages. The intervention provides them with a protective space (a club) where they can …nd support, receive information on health/reproductive issues and vocational training. Unexpectedly, the post-baseline period coincided with the 2014 Ebola outbreak. Our analysis leverages quasi-random across-village variation in the severity of Ebola-related disruption, and random assignment of villages to the intervention to document the impact of the Ebola outbreak on the economic lives of 4 700 women tracked over the crisis, and any ameliorating role played by the intervention. In highly disrupted control villages, the crisis leads younger girls to spend signi…cantly more time with men, out-of-wedlock pregnancies rise, and as a result, they experience a persistent 16pp drop in school enrolment post-crisis. These adverse e¤ects are almost entirely reversed in treated villages because the intervention enables young girls to allocate time away from men, preventing out-of-wedlock pregnancies and enabling them to re-enrol in school post-crisis. In treated villages, the unavailability of young women leads some older girls to use transactional sex as a coping strategy. The intervention causes them to increase contraceptive use so this does not translate into higher fertility. Our analysis pinpoints the mechanisms through which the severity of the aggregate shock impacts the economic lives of young women, and shows how interventions in times of crisis can interlink outcomes across younger and older cohorts. JEL Classi…cation: I25, J13, J24.
Keywords: ___working_potential_duplicate

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Government of Sierra Leone; UNICEF, 2018)

Mission and Vision - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education Republic of Sierra Leone, Government of Sierra Leone, 2018)

Statement from the Minister - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education, Government of Sierra Leone, 2018)

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found